Legislative Regulation of the Production of Organic Agricultural Products in Ukraine - Bahai, Nadiia (Journal of Vasyl Stefanyk Precarpathian National University, 2018)
The article analyzes the legislation on the production of organic agricultural products in Ukraine. Legal acts regulating the relationships in the sphere of production and circulation of organic agricultural products (raw materials) are analyzed. The main scientific approaches to the further development of national legislation on the production of organic agricultural products are investigated. The article formulates the suggestions on the improvement of legal regulation of organic production in Ukraine as well as on the adaptation of Ukrainian legislation on the production of organic agricultural products (raw materials) to the EU legislation.